Analysis of Resistance and Flow Velocity on Barge Skeg VariationsUsing Computational Fluid Dynamics Method - Chintya Intan Prastika; Priyambodo Nur Ardi Nugroho; Desi Tri Cahyaningati (National Research and Innovation Agency (BRIN Publishing), 2024)
The maritime sector utilizes various technologies, including barges, which rely on tugboats for propulsion due to lacking their propulsion system. To enhance sailing efficiency, stern modifications through skeg additions can optimize performance, though these affect drag force and velocity. This study analyzed 12 skeg variations using Computational Fluid Dynamics (CFD) simulation via ANSYS Workbench software to determine optimal design configurations. At 4 knots, the analysis revealed variation 3 as the most efficient design, producing a drag force of 17,775.80 N and velocity-u of 2.07198 m/s. Similarly, at 8 knots, variation 3 maintained optimal performance with a drag force of 67,405.60 N and velocity-u of 4.1430 m/s. Results demonstrated that variation 3 consistently provided the most stable and optimal performance across low and high speeds. These findings provide valuable insights for future barge design considerations, offering a reliable reference for selecting optimal skeg configurations.